The association between myopia and health-related quality of life among Chinese children in primary and secondary school: A cross-sectional study - Shijie Yu; Wei Sun; Hongpo Yin; Jianfeng Wu; Hongsheng Bi (PLoS ONE, 2025)
Background: Previous study on the relationship between myopia and health-related quality of life (HRQOL) among children was only conducted within hospital setting, and this relationship in school environment remained unknown. This study aimed to investigate the association between myopia and HRQOL among Chinese children aged 6–15 years in primary and secondary school. Methods: This cross-sectional study included 1,634 children, all of whom underwent routine eye examinations including cycloplegic autorefraction. The EQ-5D-Y was used to assess HRQOL. Multiple linear regression models were performed to investigate the association of myopia with EQ-5D-Y utility index (UI) values and visual analogue scale (VAS) scores. Results: Among all children, 695 (43.53%) were diagnosed with myopia ranging from -0.5 to -10.5 diopters; the mean age was 9.38 ± 2.23 years old; 838 (51.29%) were boys, and 796 (48.71%) were girls. Compared with emmetropic children, myopic children had a smaller proportion of problems with self-care and a larger proportion of problems with pain/discomfort and anxiety/depression. Children with myopia had significantly lower UI values [β = -0.008, 95% confidence interval (CI): -0.016, 0.000] and VAS scores (β = -1.300, 95%CI: -2.522, -0.078) compared to their emmetropic peers. The self-evaluation of eye health was positively associated with both UI values and VAS scores. Furthermore, decreases in UI values and VAS scores were associated to the onset of myopia, and were more pronounced in children with myopia progression. Conclusions: This study found a significant association between myopia and worse HRQOL in primary and secondary school children. These findings highlight that governments and society should pay attention to the HRQOL of myopic children.